Postmenopausal osteoporosis coexisting with other metabolic diseases: Treatment considerations. (May 2021) - Polyzos, Stergios A.; Anastasilakis, Athanasios D.; Efstathiadou, Zoe A.; Yavropoulou, Maria P.; Makras, Polyzois
Highlights: Postmenopausal osteoporosis may coexist with other metabolic diseases. Anti-osteoporotic medications may positively or adversely affect metabolic diseases. Current or emerging medications for metabolic diseases may affect bone metabolism. Abstract: In postmenopausal women, osteoporosis may coexist with other metabolic diseases, including, but not limited to, obesity, diabetes, nonalcoholic fatty liver disease (NAFLD), dyslipidemia and cardiovascular disease (CVD). This association may lie beyond simple coincidence owing to high prevalence of all these diseases, especially in the aging population, as common pathogenetic mechanisms between them and osteoporosis may exist. In this context, anti-osteoporotic medications may affect the pathogenesis of some of these metabolic diseases; this is an important consideration when selecting the most appropriate medication for osteoporotic patients with coexistent metabolic diseases. Conversely, some current or emerging medications for metabolic diseases adversely affect bone metabolism and, if possible, should be avoided in women with postmenopausal osteoporosis. The main aim of this review is to summarize the evidence on anti-osteoporotic treatment in postmenopausal women with concomitant metabolic diseases, i.e. obesity, diabetes, NAFLD, dyslipidemia and CVD. The secondary aim is to present data on the effect of current or emerging medication for metabolic diseases on bone metabolism of postmenopausal women. Deeper understanding of the underlying links between osteoporosis and metabolic diseases may have clinical implications. However, mechanistic studies are needed to elucidate the potential pathophysiological links, as well as clinical trials in women with postmenopausal osteoporosis coexisting with specific metabolic diseases; these may guide clinical practice in the future for the selection of the best anti-osteoporotic medication for each patient with specific metabolic diseases.